2023
DOI: 10.1088/1755-1315/1220/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Bird diversity in several land use types in Boyolali, Central Java

Abstract: Land use changes were thought to affect the diversity and feeding guilds of bird species. This research aims to determine the effect of five land use types (rice fields, settlements, cropland, tree plantation, and secondary forest) on species diversity and feeding guilds of bird species in Boyolali Regency. Methods used were the standard point count and the MacKinnon species list. Bird data were analyzed using the Margalef richness index, Shannon-Wiener diversity index, Pielou evenness index, and Sorensen comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The results of this study are inversely proportional to the research by (Dewi et al, 2007) conducted in Gunung Ciremai National Park, which found more birds in the primary forest namely 62 species. Meanwhile, other research that is in line with this research indicated that other habitats decreased bird numbers while secondary habitats increase the richness of bird species (Rohman et al, 2023;Tu et al, 2020). This can occur due to differences in the diversity of vegetation types in secondary and primary forests, the number of days, and observation plots.…”
Section: Bird Communitiessupporting
confidence: 77%
“…The results of this study are inversely proportional to the research by (Dewi et al, 2007) conducted in Gunung Ciremai National Park, which found more birds in the primary forest namely 62 species. Meanwhile, other research that is in line with this research indicated that other habitats decreased bird numbers while secondary habitats increase the richness of bird species (Rohman et al, 2023;Tu et al, 2020). This can occur due to differences in the diversity of vegetation types in secondary and primary forests, the number of days, and observation plots.…”
Section: Bird Communitiessupporting
confidence: 77%